MEKANISME SERTIFIKASI GURU DALAM JABATAN DAN KINERJA (Studi Kasus pada SD No 17 Arga Makmur) - Yuni Indah (UNIVED PRESS, Universitas Dehasen Bengkulu, 2016)
Certification of teachers is an education policy that applied since passed the Law on Teachers and Lecturers No. 14 of 2005. This research discusses the mechanism of certification and post-certification teacher working. This research used a qualitative descriptive approach. Data collected is done by in-depth interviews, obsservasi, methods of visual materials (photographs) and online search. Data analysis was conducted using interactive analysis Miles and Huberman. Based on the research results revealed that the mechanism of certification of teachers in North Bengkulu district has been going well, although still encountered some obstacles in the field. These constraints include: the socialization process in-service teacher still not up to it in view of the false teachers still encountered in filling the A1 format. Found 50% of elementary school in certification of teacher lack participants to have ability on computer information technology and is unable to access the online announcement of certification candidates. Pattern certification portfolio and PLPG considered to have advantages and disadvantages. In general, the performance of elementary school teachers who are already certified educator in SD N N0 17 Argamakmur district, has shown positive changes, although not yet able to satisfy the various parties such as government agencies and private institutions. Keywords: mechanism, certification of teachers in position, performance